Analysis of Students' Errors in Solving Circle Problems Based on Newman's Error Analysis - Qory, Qory Septiani Arsandy; Meridina, Ramanda; Rahmah, Khalida; Fauzi, Muhammad Amin (Edukasi, 2025)
Students' understanding of mathematical concepts is still a challenge, especially in solving problems that require procedural and conceptual understanding, such as on the topic of circles. This study aims to analyze the types of errors made by students in solving mathematical problems on the topic of circles using the Newman's Error Analysis (NEA) procedure. The approach to this study is descriptive qualitative, conducted at SD 050661 Kwala Bingai with 20 subjects of grade VI-A. Data were collected through written tests and analyzed using five stages of NEA: reading errors, understanding, transformation, process skills, and writing final answers. The results of the study showed that most students made errors at the stages of understanding, transformation, and process skills. Factors causing errors include lack of conceptual understanding, procedural errors, and inaccuracy in solving problems. The conclusion of this study shows the need for an active role for teachers in identifying and overcoming student errors through appropriate teaching methods, especially on the topic of circles. This study is expected to provide an overview for teachers in designing appropriate learning strategies to improve students' understanding of mathematical concepts.